Analysis Effect of BI Rates, Inflation and Exchange Rates on the Composite Stock Price Index on the Indonesia Stock Exchange 2016-2021 - Hanitha, Vivin; Yoyo, Toni; Silaswara, Diana (AKUNTOTEKNOLOGI : JURNAL ILMIAH AKUNTANSI DAN TEKNOLOGI, 2022)
The important role of the capital market today affects the economy of a country. Capital market performance can be measured in shares which are based on an index called the Composite Stock Price Index. By using the index, investors can find out the level of economic growth and investment development in a country. This study uses macroeconomic variables, namely interest rates (BI rates), inflation rates, and exchange rate movements. The data used is secondary data with 72 observations. The sampling method used purposive sampling method for the period 2016-2021 at Jakarta Composite Index that processed using Eviews 10. The results for this study conclude that the BI rate, inflation rate, and exchange rate have a negative value and significant effect on the Jakarta Composite Index. BI rates, inflation rate, and the exchange rate IDR/USD have no effect simultaneously with the R2 value is 0.06427 or 6.47%. The otherside is influence by variables that not examined in this research.